Multi-Point Mapping of Thunderstorm Electrical Structures - Fischer, Cameron Ivans (Proceedings of the Wisconsin Space Conference, 2022)
Electric field measurements are necessary to understand thunderstorm evolution and lightning initiation. However, most existing measurements are made with single instruments carried by weather balloons. It is difficult to interpret such data since a change in observed electric field could be due either to motion of the instrument or charging/discharging currents. In order to decouple these behaviors, it is necessary to make simultaneous measurements at multiple locations. To avoid the complexity of multiple balloon launches, we describe a single balloon instrument with multiple, independent dropsondes to be released at desired time intervals. The dropsondes are designed to rotate and be self-stabilizing, enabling them to measure electric fields as they fall. The dropsondes are lightweight, robust, and low-cost, and include a preamplifier, GPS receiver, search coil and accelerometer for orientation sensing, microcontroller, and a telemetry system to transmit data to a ground station. Prototype instruments have been drop-tested to demonstrate aerodynamic stability and rotation and have been calibrated for electric field measurement. A balloon payload set to release a set of such dropsondes via hot-wire release mechanisms can thus accomplish the goal of multi-point measurements of thunderstorm electrical structures.